Assessing the hospital survey of patient safety culture. A review of the assumptions, methods and data analysis protocol - Azevedo, Kevin Barros (2018)
Patient safety theme is becoming one of the most discussed theme in healthcare facilities, mainly at hospitals. The main aim of this paper was to present a review of the structure Hospital Survey on Patient Safety Culture model (HSOPSC) and analyze in a brief summary of the main researches that were developed recently using this survey model to explain the patient safety culture dimensions. This instrument was created by the Agency for Healthcare Research and Quality (AHRQ) and became a survey commonly used in the United States of America and increasingly used internationally, with or without adaptations.